PSYCHOLOGICAL DISTRESSES AND SOCIAL- EMOTIONAL ASSETS: THE CASE OF THE FEMALE SURVIVORS OF INCEST AT WOMEN AND CHILDREN PROTECTION CENTER - Joson, Kathreen C. (International Journal of Psychosocial Rehabilitation, 2020)
The issue of documented sexual abuse which are incest in nature is very alarming in our society nowadays. The study determined the psychological distresses and the social-emotional assets of female survivors of incest at Women and Children Protection Center, Alibagu Ilagan City, Isabela. Employing the descriptive-correlational design and case study method, the research involved the fifteen incest survivors who are temporarily housed at the Women and Children Protection Center. It also utilized the standardized tests, the Problem Behavior Inventory and the Social Emotional Assets Scales, which were translated in Filipino for better understanding. Data were analyzed using the frequency and percentage, arithmetic mean and Pearson r. In view of the findings of the study, the research conclude that majority of the female children incest survivors are 6 to 15 years old, eldest and middle child, living with their father, parents and relatives, with parents’ marital status as living together and separated. Majority of respondents’ fathers are engaged in tricycle driving and farming; their mothers as vendor, laundry woman, housewife and Overseas Filipino Workers. Most of the incest survivors’ families belong to the Food Threshold Level with a monthly earning of 6, 125.00 Php; with place of residence located in the far-flung rural areas. Most of the age range of the sexual abuse onset is 6-15 years old, perpetrated by their biological fathers; having the perpetrators’ criminal case status as on-going. The most common psychological distresses experienced by female children incest survivors after being sexually abused by the perpetrators were the somatic disorder, mood disorder, anxiety disorder, sleep disorder, and parent-child problem. The level of the emotional assets of the female children incest survivors, particularly self-regulation and responsibility is average to high functioning, while the level of respondents’ empathy, self-competence and total emotional assets is at risk. Those survivors of incest with fathers who worked as tricycle drivers and farmers while respondents’ mothers serving as housekeepers, laundry women and vendor with parents ‘place of occupation found in the barrio tended to perform higher level of social emotional assets. The more the female survivors of incest experienced eating disorder and academic problem as their psychological distresses, the lesser is the level of their self-regulation as social emotional assets; the greater is the respondents’ mood disorder as psychological distress, the lesser is the level of social competence and responsibility as social emotional assets; and the greater is the conduct disorder as psychological distress of the female survivors of incest, the lower is their total social emotional assets. This implies further that the more the female survivors of incest experience psychological distresses, they are more likely to manifest lower social emotional assets.